Physico-chemical and Sensory Characteristics of Beef Sausage with the Addition of Modified Porang Glucomannan (Amorphophallus muelleri Blume) Oleogel - Widarta, I Wayan Rai; Rukmini, Ambar; Santoso, Umar; Supriyadi, Supriyadi; Raharjo, Sri (agriTECH, 2025)
Fat is capable of affecting the physico-chemical and sensory characteristics of beef sausage. However, the use of beef fat can increase the cholesterol content, showing the need for suitable substitute such as oleogel. Therefore, this research aimed to evaluate the ability of rice bran oil oleogel prepared with modified porang glucomannan as a substitute for beef fat in sausage formulations. Analysis was also carried out to obtain beef sausage with the best characteristics (similar to commercial sausage/comparison formulation) which were made by substituting beef fat using rice bran oil oleogel. Sausage formulas were made with low-fat (10% oleogel or beef fat, w/w) and high-fat (20% oleogel or beef fat w/w), with beef fat serving as control. Another sausage formula with 20% (w/w) beef fat and tapioca was prepared representing the commercial beef sausage. The findings revealed that both the fat content and the replacement of beef fat with oleogel had a significant effect (p<0.05) on cooking loss and the proximate composition (moisture, ash, fat, and protein) of beef sausages. Significant effects were also observed on the texture (hardness, cohesiveness, springiness, gumminess, and chewiness) and sensory properties of the sausages. There is a significant effect on texture (hardness, cohesiveness, springiness, gumminess, and chewiness) as well as sensory characteristics of beef sausage. Substituting 20% of beef fat with oleogel resulted in the most favorable sensory characteristics, closely resembling those of the control formulation containing 20% beef fat combined with tapioca. In conclusion, rice bran oil oleogel formed from porang glucomannan as an oleogelator could be used as a substitute for beef fat in sausage processing.